Protective measures against COVID-19 and their impact on guest satisfaction and behaviour intentions: The case of the hotel industry of Serbia - Goran Perić; Sandra Dramićanin; Dejan Sekulić (Economic Themes, 2022)
After drastically changing the global tourism and hospitality industry, the current pandemic made hotel companies better understand the new situation and begin to adapt to new market developments. The hotel industry has made significant advances and changes in its business to guarantee the health and safety of guests. This research aimed to examine the consequence of hotels' protective measures against the COVID-19 virus on guest attitudes about protective measures, satisfaction and behavioural intentions. Research findings indicate the protective measures versus COVID-19 utilized by hotels in Serbia positively impact guest attitude towards the measures and guest satisfaction. In contrast, the impact on behavioural intentions is not statistically significant. Additionally, guest attitude towards the measures positively affects guest satisfaction. Guest satisfaction positively affects guest behavioural intentions, while the relationship between guest attitudes and behavioural intentions is not statistically significant.
Keywords: Z31; Z33; M31; 330; protective measures; COVID-19; guest attitude; satisfaction; behavioral intentions